Influence of net design on the capture performance of crab entangling nets - Picoy-Gonzales, Rizalyn M. (2016.)
In this study, the effects of 1) mesh size (MS) and hanging ratio (E) and; 2) net height on the capture performance of crab entangling nets were investigated. In the first experiment, a total of 1,418 individuals comprising 95 species belonging to 66 families were caught. Using 2-way ANOVA, no interaction between mesh size and hanging ratio was foundMesh size significantly affects the weight, number and CPUE of the total catch but has no significant effect on the same parameters of the target catch Portunus pelagicus. Hanging ration significantly affects weight, number and CPUE of both total and target catch. It also affects the catch species richness. In the second experiment, a total of 1,290 individuals comprising of 87 species belonging to 53 families were caught. One-way ANOVA showed that net height significantly affects the weight, number and CPUE of total catch. With target catch, net height has no effect on the number and CPUE (indv/hr) but significantly affects the weight and CPUE (g/hr). Capture of non-target species and catch species richness were affected by both mesh size and net height. Results suggest that increasing mesh size is a potential technical measure to reduce non-target species up to 60% in weight and 79% in number without significantlyaffecting the target catch. Catch species richness was also reduced up to 62% in larger mesh sizes. However, increasing hanging ratio may not be a good option since it significantly reduced target catch by 38% both in weight and number while maintain non-target species. Still, catch species richness decreased by 19% in a higher hanging ratio. The use of appropriate net height is another potential technical measure for a selective but still efficient crab weight and 79% in number without significantly affecting the number of the target catch. While lower nets decreased the weight of the target catch up to 65% in 12 MD, weight in 24 MD was not lower nets. Results are useful to fisheries managers and government institutions to develop or improve existing regulations towards a sustainable crab fishery particularly blue swimming crabs. .
Thesis (M.S. Fisheries-Fisheries Biology) -- Magao, Iloilo : Institute of Marine Fisheries and Oceanology, College of Fisheries, University of the Philippines Visayas, June 2016.
Keywords: Crab entangling nets; Mesh size; Portunus pelagicus